The impact and recovery of asteroid 2018 LA. (23rd April 2021) - Jenniskens, Peter; Gabadirwe, Mohutsiwa; Yin, Qing‐Zhu; Proyer, Alexander; Moses, Oliver; Kohout, Tomas; Franchi, Fulvio; Gibson, Roger L.; Kowalski, Richard; Christensen, Eric J.; Gibbs, Alex R.; Heinze, Aren; et al.
Abstract: The June 2, 2018 impact of asteroid 2018 LA over Botswana is only the second asteroid detected in space prior to impacting over land. Here, we report on the successful recovery of meteorites. Additional astrometric data refine the approach orbit and define the spin period and shape of the asteroid. Video observations of the fireball constrain the asteroid's position in its orbit and were used to triangulate the location of the fireball's main flare over the Central Kalahari Game Reserve. Twenty‐three meteorites were recovered. A consortium study of eight of these classifies Motopi Pan as an HED polymict breccia derived from howardite, cumulate and basaltic eucrite, and diogenite lithologies. Before impact, 2018 LA was a solid rock of ~156 cm diameter with high bulk density ~2.85 g cm −3, a relatively low albedo pV  ~ 0.25, no significant opposition effect on the asteroid brightness, and an impact kinetic energy of ~0.2 kt. The orbit of 2018 LA is consistent with an origin at Vesta (or its Vestoids) and delivery into an Earth‐impacting orbit via the ν6 resonance. The impact that ejected 2018 LA in an orbit toward Earth occurred 22.8 ± 3.8 Ma ago. Zircons record a concordant U‐Pb age of 4563 ± 11 Ma and a consistent 207 Pb/ 206 Pb age of 4563 ± 6 Ma. A much younger Pb‐Pb phosphate resetting age of 4234 ± 41 Ma was found. From this impact chronology, we discuss what is the possible source crater of Motopi Pan and the age of Vesta's Veneneia impact basin.